2017
DOI: 10.3389/fneur.2017.00089
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy Bodies: Molecular Pathology in the Frontal Cortex in Typical and Rapidly Progressive Forms

Abstract: ObjectivesThe goal of this study was to assess mitochondrial function, energy, and purine metabolism, protein synthesis machinery from the nucleolus to the ribosome, inflammation, and expression of newly identified ectopic olfactory receptors (ORs) and taste receptors (TASRs) in the frontal cortex of typical cases of dementia with Lewy bodies (DLB) and cases with rapid clinical course (rpDLB: 2 years or less) compared with middle-aged non-affected individuals, in order to learn about the biochemical abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 142 publications
2
40
0
1
Order By: Relevance
“…TASRs are significantly upregulated in frontal cortex in PD and DLB , and our findings further indicate that deregulation of TASRs in frontal cortex occurs in iLBD as well. Previous studies have shown altered protein synthesis machinery in the frontal cortex in PD and DLB from the nucleolus to the ribosome . Nuclear alterations include increased nucleolar stress and altered synthesis of ribosomal RNAs, in addition to altered production of mRNAs.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…TASRs are significantly upregulated in frontal cortex in PD and DLB , and our findings further indicate that deregulation of TASRs in frontal cortex occurs in iLBD as well. Previous studies have shown altered protein synthesis machinery in the frontal cortex in PD and DLB from the nucleolus to the ribosome . Nuclear alterations include increased nucleolar stress and altered synthesis of ribosomal RNAs, in addition to altered production of mRNAs.…”
Section: Discussionsupporting
confidence: 76%
“…Another deregulated cluster in LBD is related to innate inflammatory responses. This has been the subject of two detailed studies in PD and DLB (34,38). An interesting aspect was the downregulation of cytokines and several mediators of the inflammatory response in the substantia nigra at early stages of PD (34) and the relatively low inflammatory response in the frontal cortex in DLB (38), which is in line with previous observations pointing out the relatively low inflammatory response and enhanced dystrophic microglia in DLB (2,88,90).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Inflammatory responses are disease‐, region‐ and stage‐dependent, thus largely differing in AD, tauopathies, CJD, PD, DLB and ALS . Several cytokines and mediators are expressed in reactive astrocytes in these diseases, although the precise localization of individual inflammatory mediators is largely unknown.…”
Section: Astrocytopathymentioning
confidence: 99%